PENGARUH PROMOSI KESEHATAN MENGGUNAKAN METODE KONSELING TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG IMUNISASI DASAR ANAK DI WILAYAH KERJA PUSKESMAS NANGGALO PADANG - Dalina Gusti (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Of the 194 WHO member countries, 65 of whom have included Dipteri, Pertussis and Tetanus (DPT) animations under the global target of 90%. Indonesia has a slightly lower level of emissions than 2014, at 92.3% in 2015. The achievement of this indicator in Indonesia in 2015 amounted to 86.54%. This figure has not reached the target of Renstra in 2015 which amounted to 91%. The purpose of this study is to know the influence of health promotion using counseling method to improve pregnant mother's knowledge about pregnant mother's preparation on child basic immunization in working area of puskesmas nanggalo padang in 2017. Type of research is quasi experiment with one group pretest-posttest design. This research was conducted in Puskesmas Nanggalo Puskesmas Padang in March-May 2017. The population is 232 people with sample 67 people. The results of the test using kolmogorovsmirnov showed the mean rank of respondents knowledge before counseling 15.79 ± 2.136 and after counseling18.93 ± 1.271 with nilaiselisih -3.14. From statiscwilcoxon test obtained p = 0,000 (p <0,05), it can be concluded that there is a significant difference to the level of knowledge of respondents before after counseling about basic immunization in children. The conclusion before the counseling obtained mean rank 15.79, Std. Deviation 2.136, after being given counseling18,93, Std. Deviation 1.271. The Suggestion for Puskesmas is expected to health officer at Puskesmas Nanggalo Padang to motivate and give information to mothers about basic immunization in children, especially the effect that after the giving of basic immunization and contraindication.Keywords; Immunitation , Pregnant, child